Capacity building for spatial data infrastructure development (SDI) - Masser, I; Said, Ismail (2007)
An important objective for governments throughout the world is to create national spatial data infrastructures to maximise the use that is made of national geographic information assets. More than 120 countries are already considering projects of this kind. From the outset it has been recognised that building a SDI is far more than just a technical task. Their effective implementation also often requires fundamental changes in the institutional context that governs the collection and dissemination of geographical information in each of the countries involved. More recently it has also been argued that such developments will require a prolonged programme of capacity building to ensure that the most effective use is made by all of the different kinds of stakeholders that are involved of the resources provided by the creation of a SDI. For this reason it is increasingly becoming apparent that the full impacts of SDI will not be realised for decades rather than years. With these considerations in mind this paper initially examines the nature of the SDI phenomenon and then considers the needs for capacity building with particular reference to two core strategic areas in SDI development: coalition formation and institutional development for SDI implementation.